Enhancing Learning Motivation in Elementary Schools: The Impact and Role of Rewards - Sigalingging, Roslida; Nababan, Hotma; Putra, Alex; Nababan, Mandasari (Jurnal Ilmu Pendidikan dan Humaniora, 2023)
Motivation is the cornerstone of effective learning, and its cultivation begins in the elementary school years. This research delves into the relationship between rewards and students' learning motivation in elementary schools, offering valuable insights for educators, administrators, and policymakers. Employing a mixed-methods approach, the study combines quantitative surveys, qualitative interviews, and classroom observations to provide a comprehensive understanding of the dynamics at play. The research uncovers a significant positive correlation between the frequency of receiving rewards and students' academic performance, underlining the effectiveness of rewards as extrinsic motivators. However, the qualitative data reveals a more profound layer of motivation, with rewards serving as catalysts for the development of intrinsic motivation. Students describe rewards as initial sparks that gradually transition them from extrinsic to intrinsic motivation, fostering a genuine love for learning. Personalization emerges as a key factor in motivation, as tailoring rewards to individual students' interests and needs enhances long-term motivation. The positive classroom atmosphere observed in reward-rich environments contributes to engagement, enthusiasm, and overall motivation. The study provides practical implications for educators, administrators, and policymakers. It emphasizes the strategic use of rewards to motivate students, create a positive learning environment, and transition students towards intrinsic motivation. This research offers a bridge between theory and practice, empowering stakeholders to enhance the educational experience, ultimately guiding students to become lifelong learners with a passion for knowledge acquisition.